International Tradability Indices for Services - van der Marel, Erik; Shepherd, Ben (World Bank, Washington, DC, 2014)
This paper uses a theoretically grounded model of international trade to estimate the cross-border tradability of services. The resulting indices cover up to 99 countries and ten sectors. The results show that information and communications technology capital and legal institutions are particularly important determinants of a country's ability to successfully export services. The tradability indices are strongly correlated with outcome indicators, such as trade shares of individual countries. In addition, they are strongly correlated with important inputs, including country productivity and size, factor endowments, trade costs, and regulatory measures. In particular, the results suggest that a more restrictive regulatory environment significantly reduces the international tradability of services.